Peran Guru Pendidikan Agama Islam Dalam Menumbuhkan Karakter Jujur di Sd N 02 Kalibeber Wonosobo - Yeningsih Yeningsih; Sri Haryanto; Vava Imam Agus Faisal (Institut Nalanda, 2024)
The role of an Islamic Religious Education teacher plays a very important role, because as a religious teacher it is the obligation to instill positive values, for example by maintaining honesty, because honesty is the beginning of success, because being honest a person will be loved by many people and because he lives honestly. more blessing, for this reason the role of an Islamic teacher is needed which can certainly foster honest character from an early age. The problem formulation in this thesis is: 1) What is the character of the students at SD N 02 Kalibebr Wonosobo; 2) What is the role of Islamic Religious Education teachers in cultivating honest character at SD N 02 Kalibeber Wonosobo; 3) What are the inhibiting and supporting factors in developing honest character at SD N 02 Kalibeber Wonosobo. The aims of this research are: 1) To determine the character of students at SD N 02 Kalibeber Wonosobo; 2) To find out the role of Islamic Religious Education teachers in cultivating honest character at SD N 02 Kalibeber Wonosobo; 3) To determine the supporting and inhibiting factors in cultivating honest character at SD N 02 Kalibeber Wonosobo. This research uses qualitative field research. The results of the research show that: (1) The character of students at SD N 02 Kalibeber Wonosobo was found to vary, there were children who had a high honest character, some had a dishonest character, some had a disciplined character and also the character of responsibility. (2) The role of Islamic Religious Education (PAI) teachers in cultivating honest character is carried out using several strategies, . (3) Factors in the role of PAI teachers in cultivating honest character include; students' living environment close to the Islamic boarding school, adequate facilities, and also support from fellow teachers to work together to develop honest character. Meanwhile, the most important inhibiting factors are the quality of the students themselves which is difficult to change, the students' living environment which is far from TPQ and Islamic boarding schools and finally the limited teaching hours.